Two hitherto unknown Indonesian tsunamis of the seventeenth century: Probabilities and context. (22nd December 2015) - Reid, Anthony
Abstract : The 2004 tsunami intensified fruitful scientific research into dating past tectonic events in Sumatra, though without comparable work on Java. Geology needs to be informed by careful historical research on documented events, but less such work has been done in Indonesia than in other tectonically endangered areas. This paper examines the historical evidence for two hitherto unknown tsunamis of the seventeenth century. In better-researched Sumatra, Dutch reports that a flood from the sea devastated Aceh in 1660 adds to what the geologists have discovered on the ground. By contrast geological research has barely begun on the south coast of Java. Javanese sources for events before 1800 need careful re-evaluation. The myths around Ratu Kidul, the 'Queen of the South Seas', together with more chronologically reliable dated babads, point to a major tsunami in 1618 on the coast south of Yogyakarta.